Farmer participatory evaluation of legume cover crop and biomass transfer technologies for soil fertility improvement using farmer criteria, preference ranking and logit regression analysis - Nyende, P; Delve, Robert J. (Cambridge University Press, 2004)
Canavalia ensiformis, Crotalaria grahamiana, Dolichos lablab, Mucuna pruriens, Tephrosia vogellii and Tithonia diversifolia were evaluated as potential species for soil fertility replenishment in on-farm adaptive trials, farm visits and field days in Tororo District, eastern Uganda. Farmers used multiple criteria for assessing and selecting those species that fitted within their production systems and production objectives. Farmers also adapted the technologies to allow for local opportunities and constraints. A preference ranking and logit regression analysis of probabilities of acceptance of the species conducted in 19 farmer groups showed that Mucuna had high, Tithonia and Crotalaria intermediate, and Canavalia, Lablab and Tephrosia low probabilities of being accepted or adopted. The evaluations showed that whilst technologies need to be adapted, a single-use technology had little chance of large-scale adoption. This paper highlights adaptations/innovations by farmers, and opportunities for participatory action research targeting farmers' production objectives.